Evaluation of IAIN Ternate’s Interactive Marketing Communication Strategy in Increasing New Student Admissions - hamka, sufila; Novita Sari Ibn Sou; Mubaddilah Rafa’al; Niila Khoiru Amalia (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
Competition among universities to attract prospective students in the digital era demands innovative and interactive marketing strategies. This study aimed to evaluate the effectiveness of IAIN Ternate’s interactive marketing communication strategy in increasing new student admissions. This research uses a qualitative approach with a case study, involving secondary data analysis, interviews with the marketing team, and prospective students. The results indicate that IAIN Ternate has implemented various strategies, including digital marketing (website, social media, email marketing), direct outreach (roadshows to schools, campus festivals), and collaborations with alumni, religious institutions and local government. The institution’s website serves as the main hub for official information, while social media platforms such as Instagram and TikTok are used to reach younger audiences. However, the main challenges include limited human resources, budget constraints, and difficulty in creating engaging content. New student admission data from 2021 to 2024 show an increase in conversion rates (from 47% to 66.9%), despite the fluctuating number of applicants. Strategic recommendations include training the digital marketing team, improving content quality, and integrating technologies such as webinars and social media analytics. This study concludes that an interactive, digital-based communication approach has the potential to increase IAIN Ternate’s competitiveness, provided it is supported by adequate resources and content strategies relevant to prospective students’ preferences.